The effectiveness of Nusantara Instrumental As Music Therapy for Decreasing Pain In the First Stage of Labor - Amerry, Yenny; Novita, Regina Vidya Trias; Susilo, W Hary (Media Keperawatan Indonesia, 2022)
Labor pain is a series of physiological factors due to uterine contractions and cervical dilation along with mental and emotional factors. One of the non-pharmacological pain reduction techniques is music therapy in the form of Nusantara instrumental music. The research objective was to determine the differences in the distribution of music therapy on the intensity of pain during active labor in the delivery room of a private hospital in Bekasi. This study used quantitative methods and a quasi-experimental design with intervention and control. The research was conducted in June-August 2020 with a sample of 80 respondents divided into 60 intervention groups and 20 control groups. The inclusion criteria were pregnancy at term, cervical opening more than 3 cm, not under the influence of analgesic drugs, mothers who were in the caesarean section after the intervention. The results of statistical analysis using the Mann-Whitney test, a p-value of 0.000 (p <0.05) means that there is a difference in the intensity of labor pain during the active phase of the first stage mother between the intervention group and the control group.. Music therapy can be an alternative non-pharmacological nursing intervention for mothers in childbirth, so the mothers are able to control their pain and have a positive experience in childbirth